2020
DOI: 10.1007/s11356-020-08615-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica synthesized from natural local kaolin as an effective adsorbent for removing of Acid Red 337 and its application in the treatment of real industrial textile effluent

Abstract: This paper presents a synthesis of mesoporous silica (MS) from natural clay as silica sourceusing L35 pluronic(EO11PO16EO11) as structure directing agent. The prepared material wascharacterised by XRD, FRX, TGA, SEM, MET and N2 adsorption-desorption analyses. Then,mesoporous material was used for the removal of Acid Red 337 (AR337) from aqueous solution, and the treatment of real textile effluent. The effect of pH, contact time, weight of adsorbent and initial concentration wasstudied in batch adsorption. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…No obvious aggregates were observed, and silica platelets distributed randomly. Several studies reported that numerous mesopores and/or micropores could be observed in the surface of porous silica prepared from kaolinite, which largely led to increases in the specific surface area of the materials [81,82].…”
Section: Microstructure Analysismentioning
confidence: 99%
“…No obvious aggregates were observed, and silica platelets distributed randomly. Several studies reported that numerous mesopores and/or micropores could be observed in the surface of porous silica prepared from kaolinite, which largely led to increases in the specific surface area of the materials [81,82].…”
Section: Microstructure Analysismentioning
confidence: 99%
“…Due to its uniqueness, MS can be designed for various applications and uncover development opportunities related to industrial-scale mass production, which has shifted the focus of lab-scale research to the applicable research stage. Nowadays, MS is widely applied in wastewater treatment [3]- [6], air and gas purification [7], [8], catalysts [4,9], [10], food industry [11], and health industry [11]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the existing literature on the adsorption of anionic dyes and the treatment of real industrial effluent using zeolite and mesoporous materials is scarce and limited (Fardjaoui et al 2017;Slatni et al 2020).…”
mentioning
confidence: 99%
“…It is based on the enormous power of DFT (density functional theory) calculations (Casaburi et al 2021;Curcio et al 2018), as one of the most important modeling techniques to understand the intercalation process in adsorption phenomena (Ramdani, et al 2020;Slatni et al 2020), which has been greatly improved by their applications to organic materials and inorganic adsorption design (Petrosino et al 2019(Petrosino et al , 2020 2. Experimental work…”
mentioning
confidence: 99%